Analysis of the reliability referral program for patient DM type 2 health centre Sei Suka Batubara - Daffa Jihan Azmi Rambe; Sri Lestari Ramadhani Nasution; Ermi Girsang; Tan Suyono (Jurnal Scientia, 2024)
The Referral Back Program encounters various challenges in its implementation. According to BPJS Health data for the year 2017, there is a notable increase in cases of Advanced Outpatient Level (RJTL) in CMG-Q (Ambulatory Group Episodic), with a significant rise of 4.9 million cases compared to 2016. This has led to suboptimal Primary Health Care (FKTP) and an increased cost of IDR 789 billion in 2016. Stable patients tend to prefer seeking treatment at hospitals rather than returning to FKTP, and FKTPs are not fully equipped to provide pharmaceutical drug services. In terms of methodology, this research adopts a descriptive approach with a qualitative method to gain a clear and in-depth understanding of the implementation of the Type 2 Diabetes Mellitus (DM) Patient Referral Program at the Sei Suka Batubara Community Health Center. The results of the research indicate that the expected outcomes of the Disease Referral Registry (DRR) are being achieved, and there is a continuous effort to enhance service excellence. The readiness of officers implementing the referral program at Sei Suka Batubara Health Center appears to be effective, as demonstrated by the efficiency of the service process and its output. Overall, the information gathered suggests that the implementation of the Health Service Referral Program for Type 2 DM Patients is effective.